Production and post-harvest quality of custard apple irrigated with saline water and fertilized with N-P-K - Nogueira Ferreira , Fagner; Soares de Lima , Geovani; Raj Gheyi, Hans; da Silva Sá, Francisco Vanies; Sudário Dias, Adaan; Almeida dos Anjos Soares, Lauriane (Comunicata Scientiae, 2022)
Salt stress reduces plant growth and production. However, adequate fertilization can minimize the effects of salinity. From this perspective, this study aimed to assess the production and post-harvest quality of custard apple irrigated with saline water and fertilized with combinations of nitrogen, phosphorus, and potassium in the second year of cultivation. The experiment was conducted in a randomized block design and arranged as a 2 × 8 factorial with three replications, using containers adapted as drainage lysimeters in a protected environment in the municipality of Campina Grande, PB. The factors consisted of two levels of electrical conductivity of irrigation water - ECw (0.8 and 3.0 dS m-1) and eight combinations of N-P-K fertilization: 100-100-100; 100-100-125; 100-125-100; 100-125-125; 125-100-100; 125-100-125; 125-125-100; and 125-125-125% of the recommended (100%) level (100-80-40 g of N-P2O5-K2O per plant per year). Irrigation with the water salinity level of 3.0 dS m-1 reduced custard apple production in the second year. However, fertilization with the 125-100-125% N-P-K combination increased the mean fruit weight, total soluble solids, and ascorbic acid content. High irrigation water salinity negatively affected the number of segments, number of fruits, number of seeds per plant, mean fruit weight, fruit diameter, and fruit height. The 125-100-40 g N-P-K combination provided the highest values of mean fruit weight, total soluble solids, ascorbic acid content, and maturity index regardless of the salinity level. The plants grown under the ECw of 0.8 dS m-1 and 125-100-80 g of N-P-K achieved the highest total production per plant.